2007
DOI: 10.1111/j.1468-2435.2007.00396.x
|View full text |Cite
|
Sign up to set email alerts
|

Integration into the Australian Labour Market: The Experience of Three “Visibly Different” Groups of Recently Arrived Refugees1

Abstract: This paper explores the effects of "visible difference" on employment outcomes of three recently arrived refugee 2 groups: ex-Yugoslavs, black Africans, and people from the Middle East. The paper draws on data collected through a survey (150 questionnaire-based face-to-face interviews conducted by bilingual interviewers) of refugees who settled in Western Australia over the past decade. Results indicate different outcomes for respondents from the three backgrounds despite similar levels of human capital and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
156
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(172 citation statements)
references
References 23 publications
8
156
0
Order By: Relevance
“…These challenges have also been described in another research study in Australia which examined employment difficulties among 'visibly different' refugee groups (Colic-Peisker & Tilbury, 2007). African refugees appear to face particular challenges to securing employment, even those with higher levels of education.…”
Section: Main Qualitative Findingsmentioning
confidence: 99%
“…These challenges have also been described in another research study in Australia which examined employment difficulties among 'visibly different' refugee groups (Colic-Peisker & Tilbury, 2007). African refugees appear to face particular challenges to securing employment, even those with higher levels of education.…”
Section: Main Qualitative Findingsmentioning
confidence: 99%
“…Our aim was to recruit 50 participants from each group, to give a total sample of 200. For this exploratory study, given the challenges of recruitment in difficultto-access minority populations such as these (Faugier & Sargeant, 1997), we aimed for an indicative, rather than truly representative, sample (Colic-Peisker & Tilbury, 2007).…”
Section: Participant Recruitment and Interview Proceduresmentioning
confidence: 99%
“…This does not only impact on them financially, but also on their self-esteem and their mental health in general (Colic-Peisker and Tilbury 2003). This applies particularly to those who are highly qualified, as their skills and talents are often not encouraged to flourish in the new country, and in order to re-enter their profession, they need to follow longer and not always successful routes (Colic-Peisker and Tilbury 2007;Morrice, 2009;Phillimore and Goodson 2006;Shiferaw and Hagos, 2002). Participants therefore suggested that they would like to receive specific training on employment skills.…”
mentioning
confidence: 99%